Leaving a Pupil Referral Unit in Wales: Care Experienced Young People and their Post-16 Transitions - Smith, Phil (International Journal of Educational and Life Transitions, 2023)
Care experienced young people are more likely to leave compulsory schooling with fewer qualifications than their non-care experienced peers. They continue to be over-represented in school exclusion figures and are more likely to attend alternative provision such as pupil referral units (PRUs). Transitions at 16 can be difficult, particularly when support systems are lost. As such, these young people are at greater risk of homelessness, criminality and suicide, on leaving compulsory education. The risks associated with these transitions are heightened even more for those leaving alternative provision. Exploring what factors can support the transitions of PRU learners into post-16 destinations is an important line of enquiry. This article discusses qualitative findings from the first year of a three-year mixed methods study involving research with 14 PRU learners. It explores young people’s reflections on their educational journeys so far and their expectations for life after the PRU. The findings highlight how experiences of school exclusion can impact negatively on future trajectories. Despite this, the participants were still able to foresee and describe ambitious plans, supported in part by caring PRU professionals and positive role models in their lives. The article concludes by considering the factors that may facilitate or create barriers to sustainable transitions for this cohort of young people, as they begin to leave the PRUs.
Keywords: Care experienced young people; transitions; school exclusion; pupil referral unit; education other than at school; life course perspective; linked lives; Wales